OPERATION PLANNING FOR EMPTY CONTAINER REPOSITIONING - Long, Yin; Lee, Loo Hay; CHEW, Ek Peng; LUO, Yi; SHAO, Jijun; SENGUTA, Arpan; Chua, Selina M L (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
One of the challenges that liner operators face today is to effectively operate empty containers in order to meet demands and to reduce inefficiency. The objective of this study is to apply optimization techniques to solve the practical empty container repositioning problem. A decision support tool is also developed to facilitate practical applications. We present a case study which considers 49 ports and 44 services. The original problem consists of very large state space, and it might not be able to solve in reasonable time. By intelligent modeling, solutions can be provided within a few seconds. Our proposed model is compared with a simple rule which attempts to mimic the actual operation of a shipping liner. The numerical results show that the proposed model is promising. Moreover, the model is able to identify potential transshipment hubs for intra-Asia empty container transportation.